REPORT OF CHARAXICEPHALOIDES POLYORCHIS GROSCHAFT & TENORA 1978 (DIGENEA: PRONOCEPHALIDAE) IN A GREEN TURTLE - CHELONIA MYDAS (LINNAEUS, 1758) FROM BRAZIL - Cavaco, Bruna (2021)
This note reports the occurrence of Charaxicephaloides polyorchis Groschaft &Tenora, 1978 collected from a green sea turtle - Chelonia mydas (Linnaeus, 1758) from Brazil. Our specimen is larger than the original description and the following descriptions, provide new information on this species. This represents the first record with morphometric data of C. polyorchis in a green turtle from Brazil and the third record with morphometric data of this trematode.